Expanding the C-S-R framework to incorporate microbial interactions: evidence from methane-consuming communities - Wang, Rui; Chen, Yuru; Zhai, Binyan; Krause, Sascha M. B. (Frontiers in Microbiology, 2025)
Microbial interactions are critical in shaping community assembly and ecosystem functioning, yet classical ecological frameworks such as Grime’s Competitor-Stress Tolerator-Ruderal (C-S-R) model primarily emphasize individual traits, overlooking interspecies dependencies. Here, we propose an expansion of the C-S-R framework to incorporate microbial interactions, using methane-consuming communities in methane-fed microcosms as a model system. We present experimental data on both natural and synthetic methane-consuming communities derived from Lake Washington sediments, demonstrating that nitrate availability regulates community dynamics and life strategies. Under nitrogen limitation, the methanotroph Methylomonas adopts stress tolerance via nitrogen fixation but loses its competitive advantage under nitrate-rich conditions. These shifts are linked to the emergence of Methylotenera, a non-methanotrophic methylotroph that relies on cross-fed carbon from methanotrophs (e.g., Methylobacter) and alters competitive outcomes through metabolic coupling. Our findings show that survival strategies are shaped not only by intrinsic traits but also by interaction-based traits that redistribute resources and reshape ecological niches. By integrating these dynamics, we offer a novel perspective on the C-S-R framework that captures both individual and emergent behaviors, providing new insight into microbial community resilience and improving the predictive power of ecological models under environmental change.